UK economy the crisis in perspective : essays on the drivers of recent UK economic performance and lessons for the future - Giudice, Gabriele; Kuenzel, Robert; Springbett, Tom.; T&F eBooks (Milton Park, Abingdon ; New York : Routledge, 2012)
"The UK economy is one of the most widely studied and monitored in the world. This book seeks to offer detailed analysis of and information on this major subject. Comprising an edited collection of papers presented to a European Commission seminar held in June 2010 to discuss prospects for the UK economy, the book includes chapters by some of the most prominent and respected commentators on the UK economy, including Christopher Pissarides, winner of the 2010 Nobel Prize for economics, Martin Weale, recently appointed to the Bank of England's Monetary Policy Committee and Robert Chote, new chairman of the UK's Office for Budget Responsibility. The book examines the UK economy in historical perspective, analyzing the drivers of the decade of uninterrupted growth and the crash which followed it, then looks forwards to the UK's economic prospects and the policies required to optimize them. The chapters cover: fiscal policy and its impact on growth and wealth distribution; monetary policy and the Bank of England's unprecedented stimulus programme; a detailed decomposition of the sources of UK growth between 1973 and 2009; the structural excess of consumption that fuelled the UK's long boom; and the UK's labour market performance. The highly distinguished group of authors, coverage and analysis of issues central to recent UK economic history, along with the European Commission's assessment of UK economic prospects make this essential reading for economists, business and financial people, academics and students, as well for all those interested in the historical background of, and prospects for, the UK economy. Information in the chapters will be supplemented by a number of charts and tables offering information in graphic form"--
1. Introduction and overview / Gabriele Giudice, Robert Kuenzel and Tom Spingbett -- 2. Accounting for UK economic performance 1973-2009 / Ray Barrell, Dawn Holland and Iana Liadze -- 3. British labour market performance before the crisis, 1993-2007 / Christopher A. Pissarides -- 4. Unsustainable consumption : the structural flaw behind the UK's long boom / Martin Weale -- 5. The UK's external position / Robert Kuenzel -- 6. Long-term effects of fiscal policy on the size and distribution of the pie in the UK / Xavi Ramos and Oriol Roca-Sagales -- 7. The changing relationship between the UK economy and its banking sector / Tom Springbett -- 8. Policy efficacy in the crisis, exit strategies and the return of growth / E. Philip Davis and Dilruba Karim -- 9. Disease and cure in the UK : the fiscal impact of the crisis and the policy response / Rowena Crawford, Carl Emmerson and Gemma Tetlow -- 10. The government's strategy for sustainable growth / Dave Ramsden.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Financial crises -- Great Britain; Great Britain -- Economic conditions -- 1997-; Great Britain -- Economic policy -- 1997-; Electronic books